THE POWER OF ADAPTABILITY: ACHIEVING AGILITY AND QUALITY IN WEB BASED COMPANY PROFILES THROUGH EXTREME PROGRAMMING - Harjunadi Wicaksono; Jafar Shadiq; Dwi Ismiyana Putri; Rina Sayekti (Jurnal Techno Nusa Mandiri, 2023)
This study explores the utilization of Extreme Programming (XP) methodology, coupled with black box testing, in developing a Web-Based Company Profile as a supportive medium for information and promotional purposes. The objective is to optimize the effectiveness and usability of the company's online profile through an adaptive and collaborative approach. However, successful implementation of XP methodology in developing Web-Based Company Profiles relies not solely on methodological approaches. Effective project management, good team communication, and support from management are equally essential to achieve optimal outcomes. In conclusion, the integration of Extreme Programming methodology, together with black box testing, enables companies to enhance their Web-Based Company Profiles as effective mediums for information and promotional purposes. This study emphasizes the importance of adaptability, collaboration, and quality assurance in achieving successful online profiles